Adsorption of oxygenates on copper oxides : a periodic DFT study - Hernández, Diana; Jiménez Orozco, Carlos; Montillo, Sebastian; Montoya, Alejandro (2021)
A Hubbard parameter of 7 eV correctly describes the oxidation enthalpy and band gap of CuO.Methylglyoxal can be chemisorbed and activated over the CuO(111) surface to finally achieve lactic acid. A study of the adsorption modes of glycerol and lactic acid is needed before starting the reactionmechanism. A comparison between CuO and Cu2O could help to understand the high conversion andselectivity of glycerol towards lactic acid.